Photonic phase stabilizing for fiber‐radio transmission using semiconductor optical amplifier. Issue 11 (27th August 2014) - Chen, Han; Sun, Mingming; Sun, Xiaohan
ABSTRACT A novel optically controlled microwave phase stabilizing method based on semiconductor optical amplifier (SOA) is presented and the theoretical fundamentals of the design are explained. A prototype with a frequency of 10 GHz is experimentally demonstrated. It provides a stable phase drift that can be linearly compensated over 10 km single‐mode fiber with a single sideband phase noise below −100 dBc/Hz at an offset of 10 kHz by tuning the SOA injection current. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:2745–2748, 2014